Nomophobia Dynamics among Students: A Study in Indonesian Islamic Higher Education - Yogi Damai Syaputra; Deni Iriyadi; Fifi Khoirul Fitriyah; Monalisa Monalisa; Elvina Gusman; Ahmad Rofi Suryahadikusumah; Yayat Supriyadi (Islamic Guidance and Counseling Journal, 2023)
This research examines the frequent use of smartphones among college students. These conditions can lead to nomophobia behavior disorder (no mobile phone phobia). This study aims to: 1) analyze the level of nomophobia in students based on gender, faculty academic culture, and age; 2) analyze differences in nomophobia simultaneously based on gender, faculty academic culture, and age. This study uses a quantitative descriptive comparative approach. Data were obtained from 988 students at Islamic tertiary institutions. Samples were selected by convenience sampling technique. The instrument used is the nomophobia questionnaire (NMP-Q) (Yildirim, 2014), with high reliability. Data were analyzed using an Independent Sample T-test, analysis with one-way ANOVA, and two-way ANOVA analysis. The results of the study show that nomophobia among students is in the high category. This study proves that there are differences in the level of nomophobia in terms of gender where women are higher than men. Based on the faculty's academic culture and age, there is no difference in student nomophobia. There is an interaction between gender and age in influencing nomophobia. Simultaneously there was no interaction between gender, faculty academic culture, and age in determining the level of nomophobia.